PENGARUH LUASAN PENUTUPAN WADAH REMEDIASI LIMBAH CAIR BUDIDAYA UDANG VANNAME (Litopenaeus vannamei) - Dian Ayu Candra Dewi; Nanda Diniarti; Andre Rachmat Scabra (Jurnal Media Akuakultur Indonesia, 2022)
The waste in intensive culture will effect the environment around. The one way to reduce the number of waste that harm the environment is bioremediation. The biology manufacture is a process that used microbes to degrade organic pollution, such as anaerobic process. This research aims to analyze the best closing are to improve water quality in vannamei shrimp culture waste. And calculate the incubation time with different covering area to improve the water qualily. The benefits of this research are to help vanname shrimp farms to process vanname shrimp culture waste that can harm the environment. And the result of this research will be implemented in any instansion. The method that was used in this research is RAL (Completely randomized design). There are 4 treatments, this is P1 without closing (control), P2 with ½ closing, P3 with ¾ closing, P4 with complete closing, and 3 time repeating. The water quality parameters that we can check are TOM, H2S, pH, DO, turbidity, dan temperature. All the parameters are checked every 12 hours for 36 hours. The result of this research showed the best treatment to improve the water quality in vanname shrimp culture waste is ¾ closing area, and the best treatmenttime to affect the water quality is 36 hours.